Third Generation Genome Sequencing Reveals That Endobacteria in Nematophagous Fungi Esteya vermicola Contain Multiple Genes Encoding for Nematicidal Proteins - Wang, Ruizhen; Dong, Leiming; Chen, Yuequ; Wang, Shuai; Qu, Liangjian (Frontiers in Microbiology, 2022)
Esteya vermicola is the first recorded endoparasitic nematophagous fungus with high infectivity capacity, attacking the pinewood nematode Bursaphelenchus xylophilus which causes pine wilt disease. Endosymbionts are found in the cytoplasm of E. vermicola from various geographical areas. We sequenced the genome of endobacteria residing in E. vermicola to discover possible biological functions of these widespread endobacteria. Multilocus phylogenetic analyses showed that the endobacteria form a previously unidentified lineage sister to Phyllobacterium myrsinacearum species. The number of genes in the endobacterium was 4542, with 87.8% of the proteins having a known function. It contained a high proportion of repetitive sequences, as well as more Acyl-CoA synthetase genes and genes encoding the electron transport chain, compared with compared with plant-associated P. zundukense Tri 48 and P. myrsinacearum DSM 5893. Thus, this symbiotic bacterium is likely to be more efficient in regulating gene expression and energy release. Furthermore, the endobacteria in nematophagous fungi Esteya vermicola contained multiple nematicidal subtilase/subtilisin encoding genes, so it is likely that endobacteria cooperate with the host to kill nematodes.